Aluminum foil waste as catalyst for esterification of waste cooking oil - Sulaiman, Sarina; Restu, I. A. (Taylor and Francis Inc., 2019)
In this study, aluminum chloride hexahydrate (AlCl3.6 H2O) was derived from aluminum foil waste as a heterogeneous acid catalyst in the esterification of waste cooking oil. The parameters of catalyst loading (2–8 wt%), ultrasonic frequency (12–40 kHz), and reaction time (15–60 min) were optimized for maximum biodiesel yield production. Under constant condition of methanol to oil molar ratio of 6:1 and temperature of 50°C, a biodiesel yield of 91% was obtained at 2 wt% catalyst loading, 26 kHz ultrasonic frequency, and 40 min reaction time.